2019
DOI: 10.3390/genes10070536
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of Long Non-Coding RNAs in Peanut

Abstract: Long non-coding RNAs (lncRNAs) are involved in various regulatory processes although they do not encode protein. Presently, there is little information regarding the identification of lncRNAs in peanut (Arachis hypogaea Linn.). In this study, 50,873 lncRNAs of peanut were identified from large-scale published RNA sequencing data that belonged to 124 samples involving 15 different tissues. The average lengths of lncRNA and mRNA were 4335 bp and 954 bp, respectively. Compared to the mRNAs, the lncRNAs were short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 50 publications
4
24
0
Order By: Relevance
“…By comparing our results with the published peanut lncRNAs of Zhao [39], in which 50,873 lncRNAs of peanut were identified from 124 samples involving 15 different tissues, we found 39 lncRNAs were identical, accounting for about 2.7% (data shown in Table S10). The low number of identified sequences may simply reflect the small scale of the experiment, which involved only four libraries as opposed to the 124 libraries underlying the above set of lncRNAs in Zhao's [39]. In addition, the selection criteria applied here were more stringent than those commonly used.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…By comparing our results with the published peanut lncRNAs of Zhao [39], in which 50,873 lncRNAs of peanut were identified from 124 samples involving 15 different tissues, we found 39 lncRNAs were identical, accounting for about 2.7% (data shown in Table S10). The low number of identified sequences may simply reflect the small scale of the experiment, which involved only four libraries as opposed to the 124 libraries underlying the above set of lncRNAs in Zhao's [39]. In addition, the selection criteria applied here were more stringent than those commonly used.…”
Section: Discussionmentioning
confidence: 69%
“…Although a growing body of evidence supports the diverse potential roles of lncRNAs in plants, studies on lncRNAs in the cultivated peanut (Arachis hypogaea L.) largely remain unknown. Recently, Zhao et al identified 50,873 lncRNAs of peanut from large-scale published RNA sequencing data, which belonged to 124 samples involving 15 different tissues, and predicted the co-expressions of targeted genes and 386 hub lncRNAs [39].…”
Section: Introductionmentioning
confidence: 99%
“…The FEELncprogram (version 0.1.1) was used to identify lncRNAs in the transcriptome assemblies. First, the FEELnc lter was used to remove short transcripts (default 200nt) and assess single-exon transcripts [28]. The FEELnc codpot predictors were used to calculate a coding potential score.…”
Section: Identi Cation Of Lncrnasmentioning
confidence: 99%
“…The module with the highest correlation coe cient and the smallest p value was designated as the module most relevant to the trait. In this study, a signi cantly correlated module was identi ed based on a correlation coe cient (r) ≥ 0.8 [35] and p < 0.05. The co-expression networks of lncRNAs and…”
Section: Prediction Of Lncrna Functions Based On Co-expressionmentioning
confidence: 99%